Ita-Aluga: um sistema web de aluguel de imóveis para universitários - Silva, Marcelo Tavares da (Brasil, 2024)
The development of software and web systems has allowed us to create applications that support the execution of tasks and improvements in communication processes. In this context, this work aims to develop a web system that serves as a facilitator in the process of renting properties for students at the ICET-UFAM educational institution in the city of Itacoatiara-AM, enabling the visualization and facilitation of the process of searching for properties available for rent. The methodology was used in the bibliographic review stage to build the theoretical basis on the subject, in the construction of the system, based on the waterfall model and in an evaluation using the Technology Acceptance Model. The results indicate a high acceptance rate of the system, by the evaluators, which include property owners and university students at the ICET-UFAM educational institution, with this system having a good chance of being well received if made available to the target audience.